2018
DOI: 10.1152/jn.00652.2017
|View full text |Cite
|
Sign up to set email alerts
|

Neural adaptation accounts for the dynamic resizing of peripersonal space: evidence from a psychophysical-computational approach

Abstract: Interactions between the body and the environment occur within the peripersonal space (PPS), the space immediately surrounding the body. The PPS is encoded by multisensory (audio-tactile, visual-tactile) neurons that possess receptive fields (RFs) anchored on the body and restricted in depth. The extension in depth of PPS neurons’ RFs has been documented to change dynamically as a function of the velocity of incoming stimuli, but the underlying neural mechanisms are still unknown. Here, by integrating a psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 79 publications
(168 reference statements)
2
70
0
Order By: Relevance
“…Lastly related to the role of PPS in prediction, a seminal observation by Fogassi and colleagues suggested that the receptive field of PPS neurons expands when the velocity of incoming stimuli increases; as if to anticipate the moment of contact. Our group has recently demonstrated an analogous effect in humans, and by incorporating discharge adaptation in a neural network model of PPS we were able to mechanistically account for the observation . Namely, we have recently expanded on a neural network model of PPS capable of replicating the plastic nature of PPS (e.g., the fact that it expands after tool use in the far space) to now equally replicate the dynamic nature of PPS (e.g., the fact that it reshapes as a function of the velocity of the incoming stimuli) .…”
Section: Bodily Self‐consciousnessmentioning
confidence: 95%
See 1 more Smart Citation
“…Lastly related to the role of PPS in prediction, a seminal observation by Fogassi and colleagues suggested that the receptive field of PPS neurons expands when the velocity of incoming stimuli increases; as if to anticipate the moment of contact. Our group has recently demonstrated an analogous effect in humans, and by incorporating discharge adaptation in a neural network model of PPS we were able to mechanistically account for the observation . Namely, we have recently expanded on a neural network model of PPS capable of replicating the plastic nature of PPS (e.g., the fact that it expands after tool use in the far space) to now equally replicate the dynamic nature of PPS (e.g., the fact that it reshapes as a function of the velocity of the incoming stimuli) .…”
Section: Bodily Self‐consciousnessmentioning
confidence: 95%
“…Our group has recently demonstrated an analogous effect in humans, and by incorporating discharge adaptation in a neural network model of PPS we were able to mechanistically account for the observation . Namely, we have recently expanded on a neural network model of PPS capable of replicating the plastic nature of PPS (e.g., the fact that it expands after tool use in the far space) to now equally replicate the dynamic nature of PPS (e.g., the fact that it reshapes as a function of the velocity of the incoming stimuli) . That is, while the model was previously capable of mimicking behavior that resulted from manipulations in the order minutes to hours, with the inclusion of a neural adaptation mechanism, it may now account for behavioral and neurophysiological findings that occur on a trial‐per‐trial basis (e.g., whether the particular stimulus is approaching quickly or slowly).…”
Section: Bodily Self‐consciousnessmentioning
confidence: 95%
“…To suggest a putative mechanistic underpinning the observed rapid recalibration of PPS we employed a nonspiking biologically inspired neural network model that has previously been demonstrated to account for a number of PPS phenomena (Magosso et al, 2010a, b;Serino et al, 2015a;Noel et al, 2018b). Importantly, we did not attempt to build a new model from scratch to explain the rapid recalibration of PPS; contrarily, we simply took the most recent version of the model (Noel et al, 2018b) and imbued this model with Hebbian learning (as in Magosso et al, 2010a;Serino et al, 2015a) given the conceptual hypothesis that this form of learning ought in principle to account for rapid recalibration. This approach was taken as we considered it more powerful (conceptually) to demonstrate that a model already shown to account for a number of PPS phenomena can also incorporate the newly described rapid recalibration effect, than it is important to exactly fit behavioral results.…”
Section: Experiments 3 -Neural Network Modelingmentioning
confidence: 99%
“…This approach was taken as we considered it more powerful (conceptually) to demonstrate that a model already shown to account for a number of PPS phenomena can also incorporate the newly described rapid recalibration effect, than it is important to exactly fit behavioral results. Previous iterations of this model can account for sigmoidal facilitation functions , the fact that PPS has different sizes for different body parts (Noel et al, 2018b), as well as its enlargement after tool-use (Magosso et al, 2010) and as a function of increasing exteroceptive signal velocities (Noel et al, 2018b). Thus, the model simply inherited previous parameters (see Table 1 in Noel et al, 2018a), with exception of those ruling Hebbian learning (for more detail regarding the model parameters and the robustness of the its PPS encoding to parameter selection see Noel et al, 2018b.…”
Section: Experiments 3 -Neural Network Modelingmentioning
confidence: 99%
See 1 more Smart Citation